In Between Code and Knowledge Exploring Students' Computational Thinking in Analyzing Arabic Texts - Ani, Ahmad Faisal Zam; Thohir, Muhammad; Qomaruddin, Moch.; Rifqi, Arina Fadlilatar; Saputri, Intan Nur Fauziah (Institut Agama Islam Negeri (IAIN) Kediri, 2024)
Computational thinking has become a crucial skill in the 21st century, particularly in fostering critical thinking and problem-solving abilities. In their research, the Arabic Language teacher for Grade X Religion 1 at MAN 2 Banyuwangi has employed computational thinking skills in teaching Arabic text. This article aims to investigate students' computational thinking in analyzing Arabic texts. The research methodology employed a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. Data analysis utilized the qualitative analysis technique, specifically the interactive model version by Miles, Huberman, and Saldana. The research findings indicate that among the 32 students in Grade X Religion 1, all demonstrated 100% proficiency in the decomposition indicator with 32 students. In the pattern recognition stage 72% with 23 students demonstrated proficiency. Meanwhile, in the algorithmic thinking, abstraction, and generalization stages 16% with 5 students showed proficiency. Students with high computational thinking skills were able to meet all indicators, including decomposition, pattern recognition, algorithmic thinking, abstraction, and generalization. Students with moderate computational thinking skills fulfilled the decomposition and pattern recognition indicators, whereas those with low computational thinking skills only met the decomposition indicator. Thus, through the exploration of computational thinking, students are able to solve problems in analyzing Arabic text critically and creatively.